If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(5x + 2) = (8 + 5x) Reorder the terms: 5x(2 + 5x) = (8 + 5x) (2 * 5x + 5x * 5x) = (8 + 5x) (10x + 25x2) = (8 + 5x) Remove parenthesis around (8 + 5x) 10x + 25x2 = 8 + 5x Solving 10x + 25x2 = 8 + 5x Solving for variable 'x'. Reorder the terms: -8 + 10x + -5x + 25x2 = 8 + 5x + -8 + -5x Combine like terms: 10x + -5x = 5x -8 + 5x + 25x2 = 8 + 5x + -8 + -5x Reorder the terms: -8 + 5x + 25x2 = 8 + -8 + 5x + -5x Combine like terms: 8 + -8 = 0 -8 + 5x + 25x2 = 0 + 5x + -5x -8 + 5x + 25x2 = 5x + -5x Combine like terms: 5x + -5x = 0 -8 + 5x + 25x2 = 0 Begin completing the square. Divide all terms by 25 the coefficient of the squared term: Divide each side by '25'. -0.32 + 0.2x + x2 = 0 Move the constant term to the right: Add '0.32' to each side of the equation. -0.32 + 0.2x + 0.32 + x2 = 0 + 0.32 Reorder the terms: -0.32 + 0.32 + 0.2x + x2 = 0 + 0.32 Combine like terms: -0.32 + 0.32 = 0.00 0.00 + 0.2x + x2 = 0 + 0.32 0.2x + x2 = 0 + 0.32 Combine like terms: 0 + 0.32 = 0.32 0.2x + x2 = 0.32 The x term is 0.2x. Take half its coefficient (0.1). Square it (0.01) and add it to both sides. Add '0.01' to each side of the equation. 0.2x + 0.01 + x2 = 0.32 + 0.01 Reorder the terms: 0.01 + 0.2x + x2 = 0.32 + 0.01 Combine like terms: 0.32 + 0.01 = 0.33 0.01 + 0.2x + x2 = 0.33 Factor a perfect square on the left side: (x + 0.1)(x + 0.1) = 0.33 Calculate the square root of the right side: 0.574456265 Break this problem into two subproblems by setting (x + 0.1) equal to 0.574456265 and -0.574456265.Subproblem 1
x + 0.1 = 0.574456265 Simplifying x + 0.1 = 0.574456265 Reorder the terms: 0.1 + x = 0.574456265 Solving 0.1 + x = 0.574456265 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1' to each side of the equation. 0.1 + -0.1 + x = 0.574456265 + -0.1 Combine like terms: 0.1 + -0.1 = 0.0 0.0 + x = 0.574456265 + -0.1 x = 0.574456265 + -0.1 Combine like terms: 0.574456265 + -0.1 = 0.474456265 x = 0.474456265 Simplifying x = 0.474456265Subproblem 2
x + 0.1 = -0.574456265 Simplifying x + 0.1 = -0.574456265 Reorder the terms: 0.1 + x = -0.574456265 Solving 0.1 + x = -0.574456265 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1' to each side of the equation. 0.1 + -0.1 + x = -0.574456265 + -0.1 Combine like terms: 0.1 + -0.1 = 0.0 0.0 + x = -0.574456265 + -0.1 x = -0.574456265 + -0.1 Combine like terms: -0.574456265 + -0.1 = -0.674456265 x = -0.674456265 Simplifying x = -0.674456265Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.474456265, -0.674456265}
| x^1/3=7 | | 22t-2=10 | | 7x+8=x+44 | | 4y=-0.32 | | 5(10+2x)=130 | | y-12=3(x-1) | | -3(-7+6)-7=P-29 | | -22000=-1333.3333m | | 22-2t=10 | | 2(2y+1)=3(y-2)+6 | | 9(9y^2-1)=0 | | 9(9y^2-9)=0 | | -21000=-1333.3333m | | 6(-5x+5)=330 | | x/5-2=13 | | h=3/5(215-36) | | 18x^2-6x-8= | | 3(5x-6)-2(x-7)= | | 3(x+2)-x=5 | | 7=9b+16 | | 5x+2y=3270 | | 4x^11+24x^7= | | -2(8+5x)=-66 | | 5a-7=8 | | 5x+9=3+7x-6 | | 7.3x+7=11x+15 | | x^2+19+4x-4=180 | | -3(-7p+6)-7=p-29 | | 3ln(x+1)+2x=9 | | 4.9x-9.95=2.3 | | (t/9)-9=11 | | 69=x^2-4 |